Loss of Long-Term Potentiation at Hippocampal Output Synapses in Experimental Temporal Lobe Epilepsy - Grosser, Sabine; Buck, Nadine; Braunewell, Karl-Heinz; Gilling, Kate E.; Wozny, Christian; Fidzinski, Pawel; Behr, Joachim (Frontiers in Molecular Neuroscience, 2020)
Memory consolidation strongly depends on an intact dialog between the hippocampus and neocortical structures. Deficits in hippocampal signal transmission are known to provoke disturbances in memory formation. Patients suffering from temporal lobe epilepsy show severe problems in hippocampus dependent memory consolidation. In the present study, we investigate changes of synaptic plasticity at hippocampal output structures in an experimental animal model of temporal lobe epilepsy. In pilocarpine-treated rats, we found suppressed long-term potentiation (LTP) in hippocampal and parahippocampal regions such as the subiculum and the entorhinal cortex. Subsequently we focused on the subiculum, serving as the major relay station between the hippocampus proper and downstream structures. In control animals, subicular pyramidal cells express different forms of LTP depending on their intrinsic firing pattern. In pilocarpine-treated rats, however, the intrinsic firing pattern of subicular neurons may be altered due to changes in channel expression during epileptogenesis that make it difficult to satisfactorily prove the cells’ identities. However, in line with our extracellular recordings, we could show that LTP could only be induced in a minority of subicular pyramidal neurons. Intriguingly, we could demonstrate that a well-characterized cAMP-dependent signaling pathway involved in presynaptic forms of LTP is perturbed in pilocarpine-treated animals. Our findings suggest that in temporal lobe epilepsy, disturbances of synaptic plasticity may influence the information flow between the hippocampus and the neocortex.